Falsafah ‘Merdeka Belajar Kampus Merdeka’ dan Implikasinya pada Strategi Belajar: Critical Synthesis Review - Ahmad Sulaiman; Umi Salamah Umi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The presence of the Merdeka Belajar Kampus Merdeka (MBKM) policy is an attempt by the government to address Indonesia's education problems. Unfortunately, he received mixed responses from the public. Some see it as a purely electoral political strategy, while others understand the policy's ability to improve the quality of education and Indonesia's human resources. The responses that emerged were mainly then directed at learning strategies that became praxis in classes at every level of education. This research is interested in investigating and evaluating the philosophical foundations of the MBKM policy from the views of Indonesian practitioners and academics. The research method used is critical synthesis review with material for analysis in the form of scientific articles with the criteria: published within the last five years, reviewing MBKM and written by Indonesian researchers. The results of the review showed that the majority considered that there were problems in the MBKM educational philosophy which tended to encourage neoliberalization and individualization. The implication is that teachers or lecturers tend to apply learning strategies that focus on individuals and direct learning to industry or market needs.